Network pharmacology identification and in vivo validation of key pharmacological pathways of Qin Jiao for gout and arthritis - Xiaoxiong Yang; Yu Wang; Xueli Ding; Shanshan Ju; Xiaoye An; Bing Zhang; Zhijian Lin (Taylor & Francis Group, 2023)
AbstractContext: Gout is a chronic disease that imposes a huge financial and health burden on patients, which might diminish quality of life. Qin Jiao, a perennial herb found in northwestern China and Japan, is commonly used for treating various ailments.Objective: This study investigates the effects of Qin Jiao on gout and joint inflammation and elucidates its potential mechanism for gouty arthritis.Materials and methods: Study 1, a literature review was conducted using PubMed, Web of Science, and CNKI to assess the applications of Qin Jiao in arthritis treatment. Study 2 was performed to discover the component targets and gouty disease targets via TCMSP, OMIM, GeneCards and DRUGBANK, and network pharmacology analysis. Study 3, male Sprague-Dawley (SD) rats were divided into normal, model, colchicine, Qin Jiao low-dose (QJL), and Qin Jiao high-dose group (QJH), oral gavage for 40 d. Serum, synovial fluid, and synovial membrane tissue were collected to measure the expression levels of IL-1β, IL-6, and STAT3.Results: The research also identified potential targets and pharmacological pathways of Qin Jiao for gout treatment. In vivo study demonstrated Qin Jiao can reduce IL-1β levels in serum and ankle flushing fluid. ELISA analysis confirmed that Qin Jiao significantly reduces the protein expression of IL-6 and STAT3.Discussion and conclusion: Qin Jiao exerts anti-inflammatory effects on gouty arthritis by modulating the IL-6/STAT3 pathway. This study provides a biological basis for the use of Qin Jiao in treating arthritis-related diseases and offers experimental evidence for potential future drug development.